Household and plot level impact of Sustainable Land and Watershed Management (SLWM) practices in the Blue Nile: Summary of ESSP II Working Paper 42, “Household and plot level Impact of Sustainable Land and Watershed Management (SLWM) practices in the Blue Nile” - Schmidt, Emily; Tadesse, Fanaye (International Food Policy Research Institute, 2012)
This study examines the impact of sustainable land and watershed management (SLWM) on value of agricultural production and livestock holdings. Analysis suggests that plots that received investment in the first period (1992) experience a 20.6 percent higher value of production in 2010. Although value of production increases with investment, results indicate that SLWM infrastructure must be maintained for at least seven years in order to reap positive increases in value of production. Although value of production increases over time, benefits may not outweigh costs in the short term, and mechanisms to incentivize farmers to maintain the SLWM infrastructure on their plots may be needed.